Cerebrospinal fluid otorrhea masquerading as cerebrospinal fluid rhinorrhea: a rare presentation - Asharaf, Amitha A.; Mathew, Nitty; Nayak, Prateek Pandurang (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Congenital inner ear disorders are associated with cerebrospinal fluid (CSF) leaks and recurrent meningitis. Here we present a case report of a 47-year-old male patient who presented with CSF rhinorrhea and recurrent meningitis with an unidentified congenital inner disorder, which was later identified as CSF otorrhea, and had leak repair done. In this paper, we stress considering CSF otorrhea as a differential diagnosis while dealing with the presentation of recurrent meningitis.